2022
DOI: 10.1002/hsr2.457
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale screening for factor V Leiden (G1691A), prothrombin (G20210A), and MTHFR (C677T) mutations in Greek population

Abstract: Background and aims: To provide a fair estimate of the prevalence of factor V Leiden (FVL) (G1691A), prothrombin (G20210A), and MTHFR (C677T) mutations in the Greek population. Methods:We genotyped a representative sample of 974 apparently healthy Greek adults by the method of real-time PCR and we calculated the allele frequencies of factor V Leiden (FVL) (G1691A), prothrombin (G20210A), and MTHFR (C677T) mutations. In addition, we determined the frequency of co-occurrence of FVL (1691A) and prothrombin (20210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We found negative associations in all of the studied SNPs, and this was supported by previous studies of thrombophilia in the global population [41,[79][80][81][82]. Overall, the negative association results indicate that there is no risk of the studied SNPs in human diseases [83,84].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found negative associations in all of the studied SNPs, and this was supported by previous studies of thrombophilia in the global population [41,[79][80][81][82]. Overall, the negative association results indicate that there is no risk of the studied SNPs in human diseases [83,84].…”
Section: Discussionsupporting
confidence: 88%
“…Thrombophilia is commonly connected with venous thromboembolism and is considered a multifactorial disease affected by environmental and inherited risk factors, i.e., genetic variants in the FVL, PT and MTHFR genes [41]. The hematological changes associated with enhanced blood coagulability and inclination in the direction of vascular thrombosis are triggered by inherited thrombophilia [42].…”
Section: Introductionmentioning
confidence: 99%
“…FVL mutation frequency varies between different geographical regions and ethnicity. The healthy population frequency of FVL is 2%–15%, 7.5%, 12.1%, and 8.4% in Caucasians, Greece, Cyprus, and Turkey, respectively 17–19 . The healthy population frequency of FII is 4.5% and 1.2% in Greece and Turkey, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Turkey, respectively. [17][18][19] The healthy population frequency of FII is 4.5% and 1.2% in Greece and Turkey, respectively. Recent metaanalysis study in Turkey, the frequency of FVL is 7.9% in the healthy population and 22.8% in VTE patients.…”
Section: Detailed Clinical Information Of 372 Patients In the Covid-19mentioning
confidence: 99%
“…However, other studies have found that FVL-carrying males (rs6025) have 3.5-fold more fecundity than non-carriers (Van Mens et al, 2017), and that the overall rate of successful embryo transfers was higher in FVL carriers (Göpel et al, 2001), but the mechanism behind the association remains elusive. It is worth mentioning that the prevalence of the FVL mutation varies by ethnicity, with the highest rates being seen in European populations (2%-8%) (Raptopoulou et al, 2022). The highest frequency of the FVL G1691A mutation was reported in Mediterranean countries, with a prevalence of up to 15% in some populations (Bauduer & Lacombe, 2005).…”
Section: Discussionmentioning
confidence: 99%